Penyusunan Indeks Beranotasi dan Kliping Surat Kabar Singgalang Tahun 2017 Bersubjek Minangkabau Koleksi Dinas Perpustakaan dan Kearsipan Kota Padang - Selfia, Selfia; Nelisa, Malta (Program Studi Informasi, Perpustakaan, dan Kearsipan , Jurusan Bahasa dan Sastra Indonesia, 2018)
AbstractIn this paper discussed about preparation of annotated index and clipping newspapers Minangkabau charge collection Service Library and Kerasipan the city of Padang. The purpose of the writing of this paper are: 1) described the preparation of an annotated index of newspaper clippings and Singgalang Year 2017 Minangkabau charge Collection service of Library and Archival Padang city; 2) describes the constraints of drafting annotated index and clipping newspapers Singgalang Year 2017 Minangkabau charge Collection service of Library and Archival Padang city; 3) and the efforts made in the preparation of an annotated index of newspaper clippings and Singgalang Year 2017 Minangkabau charge Collection service of Library and Archival Padang city method used in the writing of this paper is research methods descriptive data gathered directly from that is the original source, namely newspapers Singgalang Collection Agency library and Archives of the city of Padang.Based on the data Analyzer, few things can be summed up as follows. The first stage in the preparation of an annotated index are: a) doing the observations on the availability of newspapers with the result there are 50 articles Minangkabau charge; b selection) newspaper articles note that newspapers charge article Singgalang Minangkabau; c) newspaper clipping creation contains information about the names of the newspapers as well as Sunrise; d) makes description newspapers listing the day, date, year published, page where articles found; e) make annotations after reading the entire contents of the article; f) determines the keywords that describe the subject matter of the problem of the article; g) making article index surta news which includes provisions in the writing of the author's name, article title and keywords; h) preparation of an annotated index of Minangkabau charge; I) annotated index, typing the title index, an index of author and keyword indices. nKedua, in the preparation of an annotated index and clipping newspapers charge Minangkabau there are obstacles faced as follows: a) constraints at the time of observation is a collection of newspapers; b) constraints at the time of selecting appropriate collection of newspapers. Third, 1) effort can be overcome with a collection of newspapers should be placed and arranged on the shelves neatly collection according to the order of the month and year of publication; 2) and effort can be overcome by grouping newspapers berdasrkan newspapers name, month and year of publication.Keywords: index, annotations, clippings, minangkabau